Aluminum alloy part and related manufacturing method
By using impregnation solutions of trivalent chromium salt and hexafluorozirconate during the anodization process of aluminum alloy parts and using a sealing solution of aluminate to form parts with a multi-layer structure, the use of hexavalent in the prior art is solved. Chromium violates health and environmental standards, achieving good corrosion resistance and paint adhesion.
Patent Information
- Application Number
- CN202380050197.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-06-28
- Publication Date
- 2025-02-21
AI Technical Summary
Existing aluminum alloy parts use hexavalent chromium in the anodization step, which violates health and environmental standards and is difficult to maintain good corrosion resistance without using hexavalent chromium.
The impregnation solution containing trivalent chromium salt and hexafluorozirconate is used to perform the impregnation step of anodized aluminum alloy parts, and the sealing step is performed using a sealing solution of aluminate to form a multi-layer structured part.
It achieves improving corrosion resistance and paint adhesion of aluminum alloy parts without using hexavalent chromium, and complies with health and environmental standards.
Smart Images

Figure CN119497767A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloy parts, and in particular to parts that have undergone anodizing steps, and in particular to parts that have undergone anodizing, impregnation and sealing steps.
[0002] The invention also relates to the field of a method for manufacturing an aluminium alloy part, in particular comprising anodising, impregnation and sealing steps. Background Art
[0003] In the aerospace industry, it is common practice to use aluminum alloy parts. Aluminum alloys offer an excellent mechanical properties / weight ratio and are relatively inexpensive to manufacture. However, depending on the environment in which they are exposed, these parts can be affected by several types of localized corrosion, causing degradation of the part and leading to its elimination or failure. In order to improve the corrosion resistance of titanium alloy parts, it is known to perform surface treatments on the parts.
[0004] The surface treatment usually includes a chromium anodizing step on the part to form an aluminum oxide surface layer with a thickness between 2μm and 15μm. Since the aluminum oxide layer is porous, the anodizing step is usually followed by a sealing step, which fills the pores in the aluminum oxide layer. This improves the corrosion resistance of the part.
[0005] The anodizing step is usually performed by immersing the part in a chromic acid solution, and the sealing step of the part is performed by immersing the part in a solution containing hexavalent chromium, which is a compound banned by new health and environmental standards.
[0006] In order to be free of hexavalent chromium, document FR-B1-3106838 proposes a surface treatment of an anodized aluminum alloy part, comprising the steps of impregnating the part by immersing it in a solution containing hexafluorozirconate and a trivalent chromium salt, and sealing the part by immersing it in a solution containing silicate. In this way, each solution used for the impregnation and sealing steps uses a compound that is a substitute for hexavalent chromium and meets safety and environmental standards. A part comprising an aluminum alloy body coated with a first layer containing aluminum oxide, an intermediate layer containing chromium and a layer containing silicate is then formed.
[0007] The present invention provides a new solution for providing parts that are corrosion resistant while meeting safety and environmental standards. Summary of the invention
[0008] To this end, the present invention proposes a part, which includes:
[0009] Aluminum alloy body,
[0010] a first layer comprising aluminum oxide and arranged on the body,
[0011] an intermediate layer comprising chromium, and
[0012] The second layer comprises aluminum oxide, and the intermediate layer is disposed between the first layer and the second layer.
[0013] The significant feature of the part according to the invention is therefore that it has a second layer of aluminium oxide. This second layer of aluminium is rich in oxygen and aluminium and gives the part very good corrosion resistance. It has also been found that this aluminium layer gives the part better paint adhesion.
[0014] As a result of the invention, the part is corrosion resistant, has good paint adhesion properties and can be manufactured while complying with health and environmental standards.
[0015] The present invention may include one or more of the following features, which may be used alone or in combination with each other:
[0016] The second layer has a thickness between 10 nm and 500 nm,
[0017] The paint layer arranged on the second layer,
[0018] The second layer is obtained by sealing the body in a sealing solution comprising aluminates.
[0019] The invention also relates to a method for manufacturing a component, comprising the following steps in chronological order:
[0020] (a) providing an aluminum alloy body,
[0021] (d) anodization of the body,
[0022] (e) impregnating the body with an impregnation solution comprising a trivalent chromium salt and a compound having an oxidizing property, and
[0023] (f) Sealing the body with a sealing solution comprising aluminate.
[0024] According to the invention, the step of sealing the aluminum alloy part is carried out using a sealing solution comprising an aluminate. It has been shown that anodized aluminum alloy parts impregnated with, for example, chromium / zirconium oxide (CrIII / Zr) and then sealed with an aluminate have good corrosion resistance, which is at least equivalent to parts sealed with silicates. In addition, aluminate sealing allows the parts to adhere better to the paint. It has also been found that aluminate sealing increases the breakdown voltage of the method. The treatment is more resistant to electrical stress.
[0025] The process also renders it free of hexavalent chromium, thus complying with safety and environmental standards.
[0026] The present invention may include one or more of the following features, which may be used alone or in combination with each other:
[0027] The sealing solution has a mass concentration of aluminate between 0.1 g / L and 10 g / L, preferably between 0.5 g / L and 5 g / L,
[0028] The aluminate is sodium aluminate,
[0029] In step (d), the body is immersed in a tank containing a sulfuric acid anodizing solution, wherein the sulfuric acid anodizing solution contains sulfuric acid at a mass concentration of between 150 g / L and 250 g / L, preferably 180 g / L.
[0030] The impregnation solution has a temperature between 30°C and 50°C, preferably 40°C,
[0031] a step (e') between steps (e) and (f) of post-impregnating the body with a post-impregnation solution comprising hydrogen peroxide and a lanthanum salt,
[0032] The oxidizing compound is hexafluorozirconate,
[0033] The sealing solution has a pH between 7 and 12, preferably 11,
[0034] The sealing solution has a temperature between 50°C and 150°C, preferably between 80°C and 100°C,
[0035] Step (f) is performed for 5 to 60 minutes, preferably 10 to 20 minutes.
[0036] Step (d) is sulfuric acid anodization,
[0037] Step (e) is performed for 5 to 60 minutes, preferably 10 to 20 minutes.
[0038] In step (f), the sealing solution comprises aluminate prior to oxidation, impregnation, post-impregnation and sealing of the body,
[0039] In step (e'), the temperature of the post-impregnation solution is between 15°C and 30°C, preferably 25°C.
[0040] The duration of step (e') is between 2 min and 30 min, preferably 5 min,
[0041] In step (e'), the body is immersed in a post-impregnation solution. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Further features and advantages will be apparent from the following description of non-limiting embodiments of the invention with reference to the accompanying drawings, in which:
[0043] Figure 1is a schematic cross-sectional view of a part according to the present invention;
[0044] Figure 2 is a schematic diagram of a method according to one embodiment of the present invention. DETAILED DESCRIPTION
[0045] According to one embodiment of the present invention, a component 1 is Figure 1 As shown. The part 1 according to the present invention comprises an aluminum alloy body 10. For example, the aluminum alloy is selected from the 2000 series, such as alloys 2014, 2017, 2024, 2214, 2219, 2618, or the 6000 series, such as alloys 6061, 6063, or the 7000 series, such as alloys 7010, 7020, 7050, 7055, 7068, 7075, 7085, 7175, 7475. According to another example, the aluminum alloy is a casting alloy of the AS7G06, AS7G03, AS10G or AS9U3 type.
[0046] The part 1 further comprises a first layer 12 arranged on the body 10. The first layer 12 comprises aluminium oxide. The first layer 12 has a thickness between 2 μm and 30 μm, preferably between 5 μm and 25 μm. The first layer 12 is obtained by anodising the part 1.
[0047] The component 1 according to the invention also comprises an intermediate layer 14 comprising chromium. The thickness of the intermediate layer 14 is between 1 μm and 10 μm, for example between 3 μm and 5 μm. The intermediate layer 14 is obtained by impregnating the component 1 with a solution comprising a trivalent chromium salt and an oxidizing compound.
[0048] The component 1 according to the invention further comprises a second layer 16. The intermediate layer 14 is arranged between the first layer 12 and the second layer 16. The second layer 16 comprises aluminium oxide 16. The second layer 16 has a thickness between 10 nm and 500 nm, preferably 200 nm. The second layer 16 is obtained by sealing the component 14 with aluminate. The second layer 16 covers the intermediate layer 14 and has its own thickness. Preferably, the component 1 further comprises a lacquer layer 18. The lacquer layer 18 is arranged on the second aluminium oxide layer 16. The lacquer layer 18 has a thickness between 10 μm and 100 μm, preferably 50 μm.
[0049] The component 1 according to the invention has good corrosion resistance and good paint adhesion. The combination of the intermediate layer 14 and the second aluminum oxide layer 16 gives the component 1 good corrosion resistance. In addition, the second aluminum oxide layer 16 improves the adhesion of the paint layer 18.
[0050] A method for manufacturing the component 1 will now be described. The manufacturing method comprises the following steps in chronological order:
[0051] (a) providing an aluminum alloy body 10,
[0052] (b) Optionally, degreasing the body 10,
[0053] (c) Optionally, immersing the body 10,
[0054] (d) anodizing of the body 10,
[0055] (e) impregnating the body 10 with an impregnation solution comprising a hexafluorozirconate and a trivalent chromium salt,
[0056] (e') Optionally, post-impregnation of the body 10,
[0057] (f) sealing the body 10 with a sealing solution comprising aluminate,
[0058] (g) Optionally, paint is applied to the main body 10.
[0059] Where applicable, aqueous compositions / solutions are completed with water up to 100% of the volume of the aqueous composition / solution.
[0060] Advantageously, the degreasing step (b) dissolves any grease present on the surface of the body 10. The degreasing step can be performed using an aqueous alkaline degreasing solution. The aqueous alkaline degreasing solution contains, for example, SOSOCLEAN A3432 in a volume concentration of, for example, 11% (volume / volume). The temperature of the aqueous alkaline degreasing solution is, for example, between 30°C and 50°C, typically 45°C. The duration of step (b) is, for example, between 1 min and 30 min, typically 10 min. Step (b) can be performed by soaking, spraying or any other technique known to those skilled in the art.
[0061] The leaching step (c) advantageously dissolves any oxide formed on the surface of the body 10. The leaching step can be performed using an aqueous alkaline leaching solution. The aqueous alkaline leaching solution comprises, for example, a mixture of SOCOSURF A1858 at a volume concentration of, for example, 42% and SOCOSURF A1806 at a volume concentration of, for example, 10% (volume / volume). The temperature of the alkaline aqueous leaching solution is, for example, between 30°C and 100°C, typically 50°C. The duration of step (c) is, for example, between 1 min and 30 min, typically 10 min. Step (c) can be performed by soaking, spraying or any other technique known to the skilled person.
[0062] Step (d) according to the invention enables the creation of a first layer 12 of aluminium oxide. At the completion of this step, the first layer 12 of aluminium oxide is porous. Advantageously, the anodising is a sulphuric acid anodising. In this step, the body 10 is immersed in a tank containing a sulphuric acid anodising solution containing sulphuric acid at a mass concentration between 150 g / L and 250 g / L, preferably 180 g / L.
[0063] The solution is in particular an aqueous solution. Preferably, the temperature of the sulfuric acid anodizing solution is between 10°C and 20°C, typically 18°C. The tank also contains an anode connected to the body 10. The anode and the body 10 are typically connected to a current generator. The body 10 is subjected to a current density of 1A / dm 2 Up to 5A / dm 2 Between, usually 2A / dm 2 The DC voltage to which the main body 10 is subjected is, for example, between 10 V and 30 V, typically between 15 V and 20 V. The duration of step (d) is between 10 min and 120 min, for example, 60 min.
[0064] The impregnation step (e) is advantageously performed by immersing the body 10 in an impregnation solution. The impregnation solution is an aqueous solution. According to the present invention, the impregnation solution comprises a trivalent chromium salt and an oxidizing compound. In the present invention, trivalent chromium refers to chromium in the +3 oxidation state.
[0065] The trivalent chromium salt may be in the form of trivalent chromium fluoride, chloride, nitrate, acetate, acetate hydroxide, sulfate, potassium sulfate, etc., such as CrF3·xH2O, CrCl3·xH2O, Cr(NO3)3·xH2O, (CH3CO2)2Cr·xH2O, (CH3CO2)7Cr3(OH)2·xH2O, Cr2(SO4)3·xH2O, CrK(SO4)2·xH2O.
[0066] The oxidizing compound according to the present invention is preferably a hexafluorozirconate. The oxidizing compound is, for example, selected from the group consisting of ammonium hexafluorozirconate ((NH4)2ZrF6), sodium hexafluorozirconate (Na2ZrF6) and potassium hexafluorozirconate (K2ZrF6).
[0067] Advantageously, the impregnation solution has a mass concentration of trivalent chromium salts between 0.5 g / L and 50 g / L and a mass concentration of compounds having oxidizing properties between 0.5 g / L and 50 g / L.
[0068] Advantageously, the impregnation solution has a temperature between 30°C and 50°C, preferably 40°C.
[0069] Advantageously, the duration of step (e) is between 5 and 60 min, preferably between 10 and 20 min.
[0070] Preferably, the impregnation solution comprises SOCOSURF TCS in a volume concentration of 34% (v / v).
[0071] Preferably, step (e') is performed with a post-impregnation solution. Step (e') is performed, for example, by immersing the body 10 in the post-impregnation solution. The post-impregnation solution is an aqueous solution containing, for example, hydrogen peroxide and a lanthanum salt. The lanthanum salt is, for example, lanthanum carbonate (La2(CO3)3).
[0072] Preferably, the impregnation solution contains SOCOSURF PACS at a volume concentration of 10% (v / v). The temperature of the impregnation solution is, for example, between 15° C. and 30° C., typically 25° C. The duration of step (e′) is, for example, between 2 minutes and 30 minutes, typically 5 minutes.
[0073] Steps (e) and optionally (e') form the intermediate layer 14 and fill the pores in the alumina layer formed in step (d).
[0074] According to the present invention, in step (f), the sealing solution is an aqueous solution containing an aluminate. The aluminate is, for example, sodium aluminate (NaAlO2), potassium aluminate (KAlO2) or lithium aluminate (LiAlO2). Preferably, the aluminate is sodium aluminate (NaAlO2). The mass concentration of aluminate is between 0.1 g / L and 10 g / L, preferably between 0.5 g / L and 5 g / L. Preferably, the sealing solution has a temperature between 50°C and 150°C, preferably between 80°C and 100°C. Preferably, the duration of this step is between 5 min and 60 min, preferably between 10 min and 20 min, and preferably, the sealing solution has a pH between 7 and 12, preferably 11. The sealing step forms the second layer 16.
[0075] Advantageously, in step (g), the lacquer is applied mechanically, for example using a spray gun, or manually using a brush.
[0076] The impregnation and sealing steps fill the pores in the alumina layer 12 and improve the corrosion resistance of the part 1. Since the sealing step is performed using aluminates, the corrosion resistance of the part 1 is improved and the paint adhesion is enhanced.
[0077] [Example]
[0078] Example 1: Corrosion test
[0079] Parts made of 2618T6 aluminum alloy and parts made of 2024T3 aluminum alloy were subjected to degreasing, immersion, sulfuric acid anodizing, dipping and post-dipping steps under the conditions listed in Table 1. Various sealing steps were then carried out according to the conditions listed in Table 2, in particular, aluminate sealing 1 according to the present invention, silicate sealing 2 according to the prior art and water sealing 3 according to the prior art.
[0080] [Table 1]
[0081]
[0082] [Table 2]
[0083]
[0084] The parts were then subjected to a salt spray test according to NF EN ISO 9227. The results are shown in Table 3.
[0085] [Table 3]
[0086]
[0087] It can be seen that seals 1 and 2 increase the corrosion resistance of the part compared to seal 3. Therefore, both silicate and aluminate seals are able to improve the corrosion resistance of the aluminum alloy part. Therefore, the aluminate seal imparts good corrosion resistance to the part, at least equivalent to the silicate seal.
[0088] Example 2: Extreme Surface Analysis
[0089] X-ray photoelectron spectroscopy (XPS) analysis was performed on the parts after sealing step 1 and sealing step 2.
[0090] The results are shown in Table 4.
[0091] [Table 4]
[0092] C O Al Si Zr N Na S F Ca Seal 1 23.7 55.4 17.0 1.0 0.3 0.5 1.0 0.1 0.9 0.2 Seal 2 33.2 47.2 - 19.4 - 0.1 - - - 0.1
[0093] Elemental analysis of the extreme surface of the part at a thickness of 50 nm showed the presence of alumina (presence of aluminum and oxygen). This alumina layer on the surface improves the corrosion resistance of the part compared to water seal and paint adhesion, as shown in Example 1.
Claims
1. A component (1), comprising: Aluminum alloy body (10), a first layer (12) comprising aluminum oxide and arranged on said body (10), an intermediate layer (14) comprising chromium, and A second layer (16) comprising aluminum oxide, the intermediate layer (14) being disposed between the first layer (12) and the second layer (16).
2. Component according to the preceding claim, wherein The second layer (16) has a thickness between 10 nm and 500 nm.
3. Component according to any one of the preceding claims, comprising a lacquer layer (18) arranged on the second layer (16).
4. A component according to any one of the preceding claims, wherein: The second layer is obtained by sealing the body (10) in a sealing solution comprising aluminates.
5. A method for manufacturing a component (1), comprising the following steps in chronological order: (a) providing an aluminum alloy body (10), (d) anodizing the body (10), (e) impregnating the body (10) with an impregnation solution comprising a trivalent chromium salt and a compound having oxidizing properties, and (f) Sealing the body (10) with a sealing solution comprising aluminate.
6. Method according to the preceding claim, characterized in that The sealing solution has a mass concentration of aluminate between 0.1 g / L and 10 g / L, preferably between 0.5 g / L and 5 g / L.
7. The method according to any one of claims 5 to 6, wherein: The aluminate is sodium aluminate.
8. The method according to any one of claims 5 to 7, characterized in that In step (d), the body (10) is immersed in a tank containing a sulfuric acid anodizing solution, wherein the sulfuric acid anodizing solution contains sulfuric acid with a mass concentration of between 150 g / L and 250 g / L, preferably 180 g / L.
9. The method according to any one of claims 5 to 8, wherein: The impregnation solution has a temperature between 30°C and 50°C, preferably 40°C.
10. The method according to any one of claims 5 to 9, further comprising a step (e') between steps (e) and (f) of post-impregnating the body (10) with a post-impregnation solution comprising hydrogen peroxide and a lanthanum salt.
11. The method according to any one of claims 5 to 10, characterized in that The oxidizing compound is hexafluorozirconate.
12. The method according to any one of claims 5 to 11, wherein: The sealing solution has a pH between 7 and 12, preferably 11.